2004
DOI: 10.1007/s11064-004-7026-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Proline on Rat Brain Activities of Alanine Aminotransferase, Aspartate Aminotransferase and Acid Phosphatase

Abstract: Hyperprolinemia type II (HPII) is an autosomal recessive disorder caused by the severe deficiency of enzyme delta1-pyrroline-5-carboxylic acid dehydrogenase leading to tissue accumulation of proline. Chronic administration of Pro led to significant reduction of cytosolic ALT activity of olfactory lobes (50.57%), cerebrum (40%) and medulla oblongata (13.71%) only. Whereas mitochondrial ALT activity was reduced significantly in, all brain regions such as olfactory lobes (73.23%), cerebrum (70.26%), cerebellum (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Interestingly, the largest study of VCFS patients reported a significantly later onset of schizophrenia in the 22q11DS patients (mean age 26 years) compared to a control group of unrelated schizophrenic patients (mean age 19 years)(Murphy et al 1999). That study along, with our finding, may thus point to etiological differences between patients with and without hyperprolinemia: Clinically elevated peripheral proline is reflected by elevation in the CNS (Baxter et al 1985; Dingman and Sporn 1959; Efron 1965; Gogos et al 1999; Jacquet et al 2003; Shanti et al 2004), and we hypothesize that the elevated plasma proline in schizophrenia also reflects elevated CNS levels in these subjects. Speculatively, it may be that chronically elevated CNS proline increases risk for development of schizophrenia, but that long-term exposure is necessary for this effect to manifest.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Interestingly, the largest study of VCFS patients reported a significantly later onset of schizophrenia in the 22q11DS patients (mean age 26 years) compared to a control group of unrelated schizophrenic patients (mean age 19 years)(Murphy et al 1999). That study along, with our finding, may thus point to etiological differences between patients with and without hyperprolinemia: Clinically elevated peripheral proline is reflected by elevation in the CNS (Baxter et al 1985; Dingman and Sporn 1959; Efron 1965; Gogos et al 1999; Jacquet et al 2003; Shanti et al 2004), and we hypothesize that the elevated plasma proline in schizophrenia also reflects elevated CNS levels in these subjects. Speculatively, it may be that chronically elevated CNS proline increases risk for development of schizophrenia, but that long-term exposure is necessary for this effect to manifest.…”
Section: Discussionsupporting
confidence: 65%
“…P5C dehydrogenase deficits and the resultant hyperprolinemia can lead to low IQ, seizures, and in some subjects, mild mental retardation (Flynn et al 1989). Following chronic proline administration, rats with plasma proline levels consistent with human HPII developed behavioral and brain histological changes coupled with impairments of glutamate synthesis, all suggestive of neurological dysfunction (Shanti et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Proline can also modulate glutamatergic neurotransmission, as supported by the specificity of proline active uptake to a subset of glutamatergic terminals, its ability to inhibit glutamate release at high concentrations, and the finding of reduced glutamate uptake in the hyperprolinemic rat brain (Phang et al, 2001; Cohen and Nadler, 1997; Ferreira et al, 2012). While studies of elevated proline in humans (22q11DS patients (Karayiorgou et al, 2004), hyperprolinemia types I and II (Phang et al, 2001)) and a chronic proline administration model (Shanti et al, 2004), have documented the pathogenic properties of hyperprolinemia, the consequences of elevated proline for CNS neurotransmission have been best demonstrated by work on the hyperprolinemic Prodh null mouse (Gogos et al, 1999; Paterlini et al, 2005), which in the presence of POX deficiency and elevated proline (peripheral and CNS), exhibits a deficit in sensorimotor gating, increased sensitivity to amphetamine, and impairments in declarative memory, coupled with locally decreased CNS glutamate and GABA, increased neurotransmitter release at glutamatergic synapses, and possible activation of dopaminergic signaling. The results of our current study therefore present a mechanism by which vitamin D insufficiency confers risk of schizophrenia; via reduced PRODH expression, proline elevation, and the concomitant dysregulation of neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…The proline dehydrogenase gene ( PRODH ), located within the common deleted region, encodes the PRODH/proline oxidase (POX) enzyme that catalyzes the first step in proline catabolism (see Supplementary Data, Figure S1). Proline is a neuromodulator at glutamatergic synapses (reviewed in Phang et al, 2001) and in humans the peripheral hyperprolinemia that can arise from mutations in PRODH , and which likely reflects CNS hyperprolinemia (Gogos et al, 1999; Paterlini et al, 2005; Dingman and Sporn, 1959; Efrom, 1965; Baxter et al, 1985; Jacquet et al, 2003; Shanti et al, 2004), has been significantly associated with cognitive impairment and decreased IQ (Raux et al, 2007), schizoaffective disorder (Jacquet et al, 2005) and schizophrenia (Clelland et al, 2011; Orešič et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…and alanine aminotransferase (ALT EC 2.6.1.2.) were isolated (Desai Shanti et al. 2004) and the activity assays performed using Infinity AST or ALT liquid assays (Thermo Electron Corporation, Vic, Australia) in the absence (control) or presence of 10 mmol/L cLeu ( n = 4).…”
Section: Methodsmentioning
confidence: 99%